Oswald (New York Simon Spotlight/Nick Jr., 2004)
Oswald the Octopus and his dog, Weenie, make many new friends when they move to Big City. The original story of Oswald and Weenie's introduction to Big City is retold in this paperback format. When they arrive at their new apartment, Oswald and Weenie realize they need help moving Oswald's piano. But who can they turn to? One by one, Oswald's neighbors lend a hand -- and soon the newcomers have made lots of new friends!
Keywords: Dogs -- Fiction; Moving, Household -- Fiction; Octopuses -- Fiction